Analysis of Entrepreneurship-Based Human Resource Management Integration to Improve Business Ecosystem Sustainability in a Dynamic Market Era: A Study in Magelang Regency - Atmaja, Hanung Eka; Widayanti, Ipuk; Ikhwan, Khairul; Aldianti, Raina Dewi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The increasingly dynamic business environment requires business actors, especially MSMEs, to adapt quickly and strategically to remain sustainable. Human resource management that is not only administrative but also oriented towards entrepreneurial values is believed to be the key to strengthening competitiveness in an era of rapidly changing markets. This study aims to analyse the effect of entrepreneurial human resource management integration on business ecosystem sustainability, with the dynamic market era as a mediating variable. This study employs an explanatory quantitative approach to examine MSMEs in Magelang Regency, Central Java. The study population consists of all active MSME actors, and through the proportionate stratified random sampling method, 71 respondents were obtained as the study sample. Primary data were collected using a Likert scale questionnaire and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS version 4.0. The results show that integrating entrepreneurial human resource management has a positive effect on market adaptability, which significantly improves the sustainability of the business ecosystem. Furthermore, the dynamic market era was found to mediate the relationship between entrepreneurial human resource management and business sustainability. This confirms that successful innovative human resource management must be accompanied by the ability to cope with changes in the external environment. These findings have important implications for strengthening MSME development strategies based on human capabilities and sustainable market adaptation.